MXene modified graphite felt electrode for vanadium battery and preparation method of MXene modified graphite felt electrode

Through the MXene modified graphite felt electrode, the problems of poor hydrophilicity and large mass transfer resistance of carbon-based electrodes are solved, and the electrochemical performance and energy storage efficiency of vanadium batteries are improved.

CN119419291AInactive Publication Date: 2025-02-11HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510013768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon-based electrodes have poor hydrophilicity, few active sites and large mass transfer resistance in vanadium batteries, which limit the electrochemical performance and energy storage efficiency of vanadium batteries operating at high current density.

Method used

MXene modified graphite felt electrode was used to react by pouring the MAX phase into ammonium hydrogen fluoride solution, then treating it in sodium hydroxide solution and ultrasonic peeling, then modifying the transition metal nitride in a quartz tube, and finally after modification The MXene powder and Nafion solution were dispersed in anhydrous ethanol, impregnated and dried in vacuo to prepare the electrode.

Benefits of technology

The hydrophilicity and conductivity of graphite felt electrodes are improved, the transmission and reaction of vanadium ions are promoted, the charge transfer resistance is reduced, and the voltage efficiency, energy efficiency and capacity retention rate of vanadium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419291A_ABST
    Figure CN119419291A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow battery electrodes, and discloses an MXene modified graphite felt electrode for a vanadium battery and a preparation method of the MXene modified graphite felt electrode. Synthesizing a composite catalyst on the surface of MXene; the composite catalyst is loaded on the graphite felt through Nafion, and the graphite felt electrode loaded with the transition metal nitride modified MXene is obtained. The MXene modified graphite felt is used, the MXene has abundant surface groups, the hydrophilicity of the graphite felt is improved, the transmission of vanadium ions on the surface of the electrode is promoted, the charge transfer resistance is reduced due to the excellent conductivity of the MXene, and the voltage efficiency and the energy efficiency of the battery are improved; a Nafion solution is used as a binder, so that the catalyst has good ionic conductivity, the catalyst is prevented from falling off in the circulation process, electron transmission is promoted, and the voltage efficiency, the energy efficiency and the capacity retention rate of the vanadium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium liquid flow batteries, and in particular to a MXene-modified graphite felt electrode for a vanadium battery and a preparation method thereof. Background Art

[0002] In a vanadium liquid flow battery (VRFB), the electrode is the core component, and its performance directly determines the overall efficiency of the vanadium battery. During the reaction process of VRFB, both the negative electrode and the positive electrode undergo the following reaction process: vanadium ions diffuse from the solution to the electrode interface, and then a series of charge transfer and electron transfer processes occur on the electrode surface; after the reaction, the product reaches the electrolyte solution through desorption and diffusion. From the perspective of electrode hydrophilicity, the electrode surface with better hydrophilicity can adsorb water molecules and vanadium ions in the solution, promoting the transmission of vanadium ions on the electrode surface. Therefore, appropriate electrode hydrophilicity can improve the ion transfer rate and reaction efficiency. Secondly, from the perspective of reaction activity, the surface activity of electrodes with rich active sites is higher. These sites provide the charge transfer path required for the reaction, increase the reaction rate, reduce the charge transfer resistance, and increase the energy density and power density of the battery. From the perspective of electrode mass transfer, the path length and channel size of the electrolyte diffusion in the electrode directly affect the rate of material transfer. Carbon-based materials (such as graphite felt, carbon felt, carbon cloth, etc.) are commonly used electrodes for vanadium batteries, with the advantages of large specific surface area and excellent chemical stability. However, their poor hydrophilicity, few active sites and large mass transfer resistance limit the operation of vanadium batteries at high current density. Therefore, solving the factors affecting the mass transfer resistance of carbon-based electrodes can effectively improve the electrochemical performance and energy storage efficiency. Summary of the invention

[0003] The object of the present invention is to provide a MXene-modified graphite felt electrode for a vanadium battery and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solutions: The present application discloses a MXene-modified graphite felt electrode for a vanadium battery and a preparation method thereof, comprising the following steps: S1. Pour the MAX phase into an ammonium bifluoride solution to form a reaction solution, stir and react at 40°C for 48 hours. After the reaction is completed, centrifuge the obtained suspension and wash it with deionized water until the supernatant is close to neutral. Then treat the obtained MXene in a sodium hydroxide solution for a period of time, and then wash it with deionized water. Ultrasonic peel the MXene powder in an ice water bath and under argon protection, centrifuge it several times and dry it to obtain the MXene powder; S2, the MXene powder is placed in a quartz tube, the temperature is raised after passing argon, and then carbon dioxide is passed for a period of time, and then ammonia is passed for a period of time after stopping, and finally cooled under the protection of argon to obtain transition metal nitride modified MXene powder; S3. The transition metal nitride modified MXene powder and 5 wt% Nafion solution are dispersed in anhydrous ethanol, followed by ultrasonic treatment, and then the graphite felt is immersed in the mixed solution, taken out and dried. After repeated immersion, the graphite felt is vacuum dried to obtain a graphite felt electrode loaded with transition metal nitride modified MXene.

[0005] Preferably, the MAX phase in step S1 is Mo 2 Ga 2 C、Nb 2 AlC、Ti 3 AlC 2 One of them, with a mass concentration of 8.3~75g / L in the reaction solution.

[0006] Preferably, the concentration of the ammonium bifluoride solution in step S1 is 1-3M.

[0007] Preferably, the concentration of the sodium hydroxide solution in step S1 is 0.5-1.5 M, and the treatment time is 2-4 h.

[0008] Preferably, in step S2, the heating rate is 2-4°C / min, and the heating time is 195-390min.

[0009] Preferably, in step S2, the carbon dioxide is introduced for 30 to 60 minutes, and the ammonia is introduced for 3 to 5 hours.

[0010] Preferably, in step S3, the mass ratio of transition metal nitride modified MXene powder, 5 wt% Nafion solution, and anhydrous ethanol is (60-100): (300-500): (23-40).

[0011] Preferably, the dipping is repeated 4 to 6 times in step S3.

[0012] A MXene-modified graphite felt electrode for a vanadium battery is prepared by using the above-mentioned method for preparing a MXene-modified graphite felt electrode for a vanadium battery.

[0013] Beneficial effects of the present invention: The present invention uses MXene to modify graphite felt. MXene has abundant surface groups, which improves the hydrophilicity of graphite felt and promotes the transmission of vanadium ions on the electrode surface. In addition, the excellent conductivity of MXene reduces the charge transfer resistance and improves the voltage efficiency and energy efficiency of the battery.

[0014] The present invention prepares transition metal nitrides in situ on the surface of MXene to construct a composite catalyst. Transition metal nitrides have higher conductivity than oxides, and the composite catalyst has higher catalytic activity, thereby improving the voltage efficiency and energy efficiency of the battery.

[0015] The present invention uses Nafion solution as a binder, which has good ionic conductivity, prevents the catalyst from falling off during the cycle, promotes the transmission of electrons, and improves the voltage efficiency, energy efficiency and capacity retention rate of the vanadium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The MoN-modified Mo prepared in Example 1 of the present invention 2 CT x Scanning electron microscope image of the graphite felt electrode.

[0017] Figure 2 The MoN modified Mo prepared in Example 1 of the present invention 2 CT x Transmission electron microscope image of the powder and mapping of its location.

[0018] Figure 3 The AC impedance diagram of the graphite felt in Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0020] A method for preparing MXene-modified graphite felt electrode points for vanadium batteries comprises the following steps: S1. Pour the MAX phase into a 1~3M ammonium bifluoride solution to form a reaction solution. The mass concentration of the MAX phase in the reaction solution is 8.3~75g / L. Stir the reaction at 40°C for 48 hours. After the reaction is completed, the obtained suspension is centrifuged and washed with deionized water until the supernatant is close to neutral. The obtained MXene is then treated in a 0.5~1.5M sodium hydroxide solution for 2~4h and then washed with deionized water. The MXene powder is ultrasonically exfoliated in an ice water bath and under argon protection, and dried after multiple centrifugation to obtain MXene powder.

[0021] S2. Put the MXene powder into a quartz tube, pass argon and heat it at a rate of 2-4°C / min for 195-390min, then pass carbon dioxide for 30-60min, then pass ammonia for 3-5h, and finally cool it under argon protection to obtain transition metal nitride modified MXene powder.

[0022] S3, 60-100 parts by mass of transition metal nitride modified MXene powder and 300-500 parts by mass of 5 wt% Nafion solution are dispersed in 23-40 parts by mass of anhydrous ethanol, followed by ultrasonic treatment. Then, the graphite felt is immersed in the mixed solution, taken out and dried. After immersion 4-6 times, the graphite felt is vacuum dried to obtain a graphite felt electrode loaded with transition metal nitride modified MXene.

[0023] Embodiment 1: This embodiment is specifically obtained by the following operations: S1. Will Mo 2 Ga 2 C was poured into 1M ammonium bifluoride solution to form a reaction solution. The mass concentration of MAX phase in the reaction solution was 25 g / L. The reaction was stirred at 40°C for 48 hours. After the reaction was completed, the obtained suspension was centrifuged and washed with deionized water until the supernatant was close to neutral. 2 CT x Treat in 0.5M sodium hydroxide solution for 2h and then wash with deionized water. 2 CT x The powder was ultrasonically exfoliated in an ice-water bath and under argon protection, centrifuged several times and dried to obtain Mo 2 CT x powder.

[0024] S2. Will Mo 2 CT x The powder was placed in a quartz tube, and the temperature was raised at a rate of 2°C / min for 390 min after passing argon. Then, carbon dioxide was passed for 30 min, and then ammonia was passed for 3 h. Finally, it was cooled under argon protection to obtain MoN-modified Mo 2 CT x powder.

[0025] S3, 60gMoN modified Mo 2 CT x The powder and 300 g of 5 wt% Nafion solution were dispersed in 23 g of anhydrous ethanol, followed by ultrasonic treatment. The graphite felt was then immersed in the mixed solution and taken out to dry. After immersion for 4 times, the graphite felt was vacuum dried to obtain a MoN-modified Mo 2 CT x Graphite felt electrode. Figure 1The MoN modified Mo in Example 1 2 CT x Scanning electron microscope image of graphite felt electrode, from Figure 1 It can be seen that MoN modified Mo 2 CT x The Nafion solution is loaded on the surface of graphite felt fiber. Figure 2 (A) is MoN modified Mo in Example 1 2 CT x Transmission electron microscopy images of the catalyst. Figure 2 (B), (C), and (D) are the mapping diagrams of Mo, C, and N elements at this position, respectively. It can be seen that Mo 2 CT x The surface Mo oxide is nitrided to MoN by ammonia gas.

[0026] Embodiment 2: This embodiment is obtained by the following operations: S1, Nb 2 AlC was poured into 2M ammonium bifluoride solution to form a reaction solution. The mass concentration of MAX phase in the reaction solution was 8.3 g / L. The reaction was stirred at 40°C for 48 hours. After the etching reaction was completed, the obtained suspension was centrifuged and washed with deionized water until the pH value of the supernatant was close to neutral. 2 CT x Treat in 1M sodium hydroxide solution for 3 h and then wash with deionized water. 2 CT x The powder was ultrasonically exfoliated in an ice-water bath and under argon protection, centrifuged several times and dried to obtain Nb 2 CT x powder.

[0027] S2, Nb 2 CT x The powder was placed in a quartz tube, and the temperature was raised at a rate of 3 °C / min for 293 min after passing argon gas. Then, carbon dioxide was passed for 45 min, and then ammonia was passed for 4 h. Finally, the tube was cooled under argon protection to obtain NbN-modified Nb 2 CT x powder.

[0028] S3, 80gNbN modified Nb 2 CT x The powder and 400 g of 5 wt% Nafion solution were dispersed in 30 g of anhydrous ethanol, followed by ultrasonic treatment. The graphite felt was then immersed in the mixed solution and taken out to dry. After immersion for 5 times, the graphite felt was vacuum dried to obtain a NbN-modified Nb 2 CT x Graphite felt electrode.

[0029] Embodiment 3: This embodiment is specifically obtained by the following operations:

[0030] S1. Ti 3 AlC 2 Pour into 3M ammonium bifluoride solution to form a reaction solution, the mass concentration of MAX phase in the reaction solution is 75g / L, and stir the reaction at 40°C for 48 hours. After the reaction is completed, the obtained suspension is centrifuged and washed with deionized water until the supernatant is close to neutral. 3 C 2 T x Treat in 1.5M sodium hydroxide solution for 4 h and then wash with deionized water. 3 C 2 T x The powder was ultrasonically exfoliated in an ice-water bath and under argon protection, centrifuged several times and dried to obtain Ti 3 C 2 T x powder.

[0031] S2, Ti 3 C 2 T x The powder was placed in a quartz tube, and the temperature was raised at a rate of 4 °C / min for 195 min after passing argon gas. Then, carbon dioxide was passed for 60 min, and then ammonia was passed for 5 h. Finally, it was cooled under argon protection to obtain TiN-modified Ti 3 C 2 T x powder.

[0032] S3, 100g TiN modified Ti 3 C 2 T x The powder and 500 g of 5 wt% Nafion solution were dispersed in 40 g of anhydrous ethanol, followed by ultrasonic treatment. The graphite felt was then immersed in the mixed solution and taken out to dry. After immersion for 6 times, the graphite felt was vacuum dried to obtain a TiN-modified TiO2-supported graphite. 3 C 2 T x Graphite felt electrode.

[0033] Comparative Example 1: This comparative example is a blank control group, that is, untreated blank graphite felt is used.

[0034] Comparative Example 2: The preparation process of this comparative example is different from that of Example 1 only in that step S2 is not performed.

[0035] Comparative Example 3: The preparation process of this comparative example is different from that of Example 1 only in that no ammonia gas is passed in step S2. Figure 3 The AC impedance diagrams of the graphite felt in Example 1, Comparative Example 2 and Comparative Example 3 are all composed of a semicircle in the high-frequency region and a straight line in the low-frequency region. The smaller the semicircle diameter in the high-frequency region, the smaller the charge transfer resistance and the higher the conductivity. The larger the slope of the straight line in the low-frequency region, the faster the ion diffusion. Example 1 has a smaller semicircle diameter and a larger straight line slope, indicating that the transition metal nitride modified MXene has a higher conductivity, so its electrocatalytic performance is improved.

[0036] The graphite felts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into battery stacks and subjected to charge and discharge tests under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, and capacity retention rate after 100 cycles were recorded. The test results are shown in Table 1: Table 1. Test results of graphite felt performance in examples and comparative examples Coulomb efficiency Voltage efficiency Energy efficiency Capacity retention rate after 100 cycles Example 1 96.7% 89.3% 86.4% 97.8% Example 2 96.5% 90.6% 87.4% 98.4% Example 3 96.8% 89.8% 86.9% 97.5% Comparative Example 1 96.2% 80.4% 77.3% 82.5% Comparative Example 2 96.5% 83.6% 80.7% 92.6% Comparative Example 3 96.3% 85.7% 82.5% 95.4% As can be seen from Table 1, compared with Comparative Example 1, Examples 1 to 3 and Comparative Example 2 have higher voltage efficiency, energy efficiency and capacity retention rate, mainly because the present invention uses MXene to modify graphite felt, MXene has rich surface groups, improves the hydrophilicity of graphite felt, and promotes the transmission of vanadium ions on the electrode surface. And the excellent conductivity of MXene reduces the charge transfer resistance and improves the voltage efficiency and energy efficiency of the battery; and Nafion solution, as a binder, has good ionic conductivity, prevents the catalyst from falling off during the cycle, promotes the transmission of electrons, and improves the voltage efficiency, energy efficiency and capacity retention rate of the vanadium battery; compared with Comparative Example 3, Examples 1 to 3 have higher voltage efficiency and energy efficiency, mainly because the present invention prepares transition metal nitrides in situ on the surface of MXene to construct composite catalysts, transition metal nitrides have higher conductivity than oxides, and this composite catalyst has higher catalytic activity, which improves the voltage efficiency and energy efficiency of the battery.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MXene-modified graphite felt electrode for a vanadium battery, characterized in that: The following steps are involved: S1. Pour the MAX phase into an ammonium bifluoride solution to form a reaction solution, stir and react at 40°C for 48 hours. After the reaction is completed, centrifuge the obtained suspension and wash it with deionized water until the supernatant is close to neutral. Then treat the obtained MXene in a sodium hydroxide solution for a period of time, and then wash it with deionized water. Ultrasonic peel the MXene powder in an ice water bath and under argon protection, centrifuge it several times and dry it to obtain the MXene powder; S2, the MXene powder is placed in a quartz tube, the temperature is raised after passing argon, and then carbon dioxide is passed for a period of time, and then ammonia is passed for a period of time after stopping, and finally cooled under the protection of argon to obtain transition metal nitride modified MXene powder; S3. The transition metal nitride modified MXene powder and 5 wt% Nafion solution are dispersed in anhydrous ethanol, followed by ultrasonic treatment, and then the graphite felt is immersed in the mixed solution, taken out and dried. After repeated immersion, the graphite felt is vacuum dried to obtain a graphite felt electrode loaded with transition metal nitride modified MXene.

2. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: In the step S1, the MAX phase is one of Mo2Ga2C, Nb2AlC, and Ti3AlC2, and its mass concentration in the reaction solution is 8.3-75 g / L.

3. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The concentration of the ammonium bifluoride solution in step S1 is 1-3M.

4. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step S1 is 0.5-1.5 M, and the treatment time is 2-4 h.

5. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: In step S2, the heating rate is 2-4°C / min, and the heating time is 195-390min.

6. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: In step S2, the carbon dioxide is introduced for 30 to 60 minutes, and the ammonia is introduced for 3 to 5 hours.

7. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The mass ratio of the transition metal nitride-modified MXene powder, 5 wt% Nafion solution, and anhydrous ethanol in the step S3 is (60-100): (300-500): (23-40).

8. The method for preparing a MXene-modified graphite felt electrode for a vanadium battery according to claim 1, characterized in that: The dipping in step S3 is repeated 4 to 6 times.

9. A MXene-modified graphite felt electrode for a vanadium battery, characterized in that: The graphite felt electrode is prepared by the method for preparing a MXene-modified graphite felt electrode for a vanadium battery as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-activity MXeneCF composite electrode material and application thereof in vanadium battery

    CN114497591A

  • Preparation method and application of modified graphite felt for vanadium redox flow pile

    CN117154105A

  • Preparation method of high-performance IL-MW-Mxene / CF composite electrode material and application of high-performance IL-MW-Mxene / CF composite electrode material in vanadium battery

    CN117497777A